Disparities in breast cancer: a multi‐institutional comparative analysis focusing on American Hispanics. (7th May 2018) - Nahleh, Zeina; Otoukesh, Salman; Mirshahidi, Hamid Reza; Nguyen, Anthony Loc; Nagaraj, Gayathri; Botrus, Gehan; Badri, Nabeel; Diab, Nabih; Alvarado, Andres; Sanchez, Luis A.; Dwivedi, Alok K.
Abstract: Breast cancer (BC) is the leading cause of cancer death in Hispanic/Latino women nationwide. Hispanic women are more likely to be presented with advanced disease and adverse prognosis subtypes. The aim of this study is to describe the clinico‐ pathological characteristics and disparities in breast cancer in this group at two tertiary care University‐based medical centers. After IRB approval, Cancer registry was used to analyze the variables of 3441 patients with breast cancer diagnosed and treated consecutively at two large tertiary University based medical and cancer center database centers in El Paso, TX and Loma Linda, CA between 2005 and 2015. Association between race/ethnicity and cancer type, stage, hormone receptor status and treatment option were investigated. Overall 45.5% of the patients were Hispanic (n: 1566) and those were more likely to be diagnosed at a younger age (57 years) similar to African Americans, more likely to have invasive ductal carcinoma type (82.7%) & triple negative disease (17.1%, 95%CI: 15% to 19%). 58.8% of Hispanics (95%CI: 56% to 61%) have hormone receptor (HR)+ & HER2− as opposed to 71% in non‐Hispanic White people. In addition, Hispanic individuals presented with advanced stages of BC (25.3%, 95% CI: 23% to 28%) similar to African American (25.4%), and had a lower proportion of lumpectomy (50%) similar to African American (50%). When compared to African American patients, Hispanic patients had a higher prevalence of triple negative BC (17.11% in Hispanics Versus 13.86% in African American). Conclusion: Hispanics had significantly higher relative risk of advanced stages at presentation (Relative Risk Ratio (RRR) = 2.05, P < 0.001), triple negative tumors (RRR = 2.64, P < 0.0001), HER2 + /HR ‐ disease (RRR = 1.77, P < 0.0001), and less HR+ /HER2− BC (RRR = 0.69, P < 0.0001). Hispanics and African Americans are diagnosed with breast cancer at a younger age, have a higher prevalence of Triple negative breast cancer, and are diagnosed at more advanced stages of disease. Increasing awareness and targeting minority populations for health promotion interventions, screening and early detection continue to be of paramount importance to reduce the burden of health disparities. Abstract : Hispanics and African Americans are diagnosed with breast cancer at a younger age, have a higher prevalence of triple‐negative breast cancer, and are diagnosed at more advanced stages of disease. Increasing awareness and targeting minority populations for health promotion interventions, screening and early detection is of paramount importance to reduce the burden of health disparities.